AI-ENHANCED DIGITAL DIDACTICS FOR THE UZBEK LANGUAGE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article discusses the possibilities of utilizing artificial intelligence in teaching Uzbek as a foreign language. The author proposes specific methodological tools and practical exercises designed to enhance students’ communicative competence in the Uzbek language.